2022
DOI: 10.18805/lr-4793
|View full text |Cite
|
Sign up to set email alerts
|

​Effect of Different Organic Sources on Growth and Seed Quality Parameters of Black Gram [Vigna mungo (L.) Hepper]

Abstract: Background: Pulses play an important role in Indian agriculture for sustainable production, improvement in soil health and environmental safety. They are a cheaper source of protein to overcome malnutrition among vegetarians due to the presence of a high percentage of quality protein which is nearly three times more than that of cereals. They are more responsive to organic manures but indiscriminate and continuous use of chemical fertilizers has venomous effects on soil physical, chemical and biological proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Effect of Rhizobium and PSB on Grain yield per hectare By the means of the data obtained in this experiment, it can be concluded that the grain yield per hectare was highest in treatment T12-100% RDF + Rhizobium + PSB that is 1741.33 kg. Similar results were obtained by (Kumar, 2011) [1] (Singh, 2011) [7] (Pankaj, 2005) [4] in their experiments too.…”
Section: Effect Of Rhizobium and Psb On Grain Yield Per Plotsupporting
confidence: 87%
See 3 more Smart Citations
“…Effect of Rhizobium and PSB on Grain yield per hectare By the means of the data obtained in this experiment, it can be concluded that the grain yield per hectare was highest in treatment T12-100% RDF + Rhizobium + PSB that is 1741.33 kg. Similar results were obtained by (Kumar, 2011) [1] (Singh, 2011) [7] (Pankaj, 2005) [4] in their experiments too.…”
Section: Effect Of Rhizobium and Psb On Grain Yield Per Plotsupporting
confidence: 87%
“…The data obtained for grain yield per plot indicated that the treatment T12-100% RDF + Rhizobium + PSB was the best performing treatment with a grain yield per plot of 2.62 Kg. the results were in conformity with (Kumar, 2011) [1] (Pankaj, 2005) [4] and (P, 2018). Effect of Rhizobium and PSB on Grain yield per hectare By the means of the data obtained in this experiment, it can be concluded that the grain yield per hectare was highest in treatment T12-100% RDF + Rhizobium + PSB that is 1741.33 kg.…”
Section: Effect Of Rhizobium and Psb On Grain Yield Per Plotsupporting
confidence: 85%
See 2 more Smart Citations